Household Prevalence of Plasmodium falciparum, Plasmodium vivax, and Plasmodium ovale in the Democratic Republic of the Congo, 2013–2014. (26th November 2020) - Mitchell, Cedar L; Topazian, Hillary M; Brazeau, Nicholas F; Deutsch-Feldman, Molly; Muwonga, Jeremie; Sompwe, Eric; Tshefu, Antoinette K; Mwandagalirwa, Melchior K; Parr, Jonathan B; Juliano, Jonathan J
Abstract: In a cross-sectional molecular study in the Democratic Republic of the Congo, 78% of households had ≥1 member infected with Plasmodium falciparum, Plasmodium vivax, and/or Plasmodium ovale spp.; 47% of children and 33% of adults tested positive for ≥1 species. Risk factors varied by species and age group.